The body in French queer thought : from writing to preciado - Evans, Elliot, 1986- (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"The Body in French Queer Thought from Wittig to Preciado: Queer Permeability identifies a common concern in French queer works for the materiality of the body, and argues for a return to the body as fundamental to queer thought and politics, from HIV onwards"--
OCLC-licensed vendor bibliographic record.
Keywords: Human body (Philosophy) -- France; Philosophy, French; Queer theory -- France; SOCIAL SCIENCE / Gender Studies